Bone Morphogenetic Protein-2 and Demineralized Bone Matrix in Difficult Bony Reconstructions in Cleft Patients - Katelyn G. Makar, MD, MS; Steven R. Buchman, MD; Christian J. Vercler, MD, MA (Plastic and Reconstructive Surgery, Global Open, 2021)
Summary:. Reconstruction of alveolar clefts includes fistula repair and bone grafting. However, bone is often harvested from the iliac crest or the skull, which can be associated with considerable donor site morbidity, and the failure rate may be as high as 20%. As such, some centers utilize bone morphogenetic protein (BMP)-2 to reconstruct the bony cleft. However, this remains an off-label use, and therefore we propose using BMP-2 only in patients with tenuous soft tissues, when the likelihood of graft failure is high. In four patients, we used BMP-2 with demineralized bone matrix (DBM) to reconstruct defects related to clefts—three patients had alveolar clefts, and the fourth patient was referred to us, with resorption of a necrotic premaxilla after premaxillary setback. In all cases, the decision was made to forego bone grafting intraoperatively given the poor quality of soft tissue and the increased risk of bone graft exposure. BMP-2 was infused onto a carrier and placed in the fistula, and Grafton DBM was then packed into the defect. In three cases, small amounts of bone from the piriform aperture were mixed with the BMP-2/DBM. After 3–7 months, all patients had generated bone in the clefts and did not require bone grafting. While we continue to prefer a “like with like” reconstruction, bone grafting has a high likelihood of failure in patients with suboptimal soft tissues or tight closures. We suggest that combining BMP-2 and DBM in higher risk patients is an excellent option to avoid bone graft loss and reoperation.